Penguatan Kesadaran Lingkungan melalui Program Bersih-bersih dan Edukasi Pemilahan Sampah - Muhammad Catur Rizky; Muhamad Sultan Sungku; Muhammad Yusron Maulana El-Yunusi; Sirojuddin Abror; Rommy Hardyansah (Universitas Pahlawan Tuanku Tambusai, 2026)
Students from Sunan Giri University in Surabaya held a community service event on December 20, 2025. They organized an environmental cleanup and taught people how to use separate trash bins for different types of waste. The reason for this event was because people still didn't understand enough about keeping things clean and properly sorting trash. The activity used the Asset Based Community Development method, which means they worked with the community and used their strengths and involvement. During the event, the community helped clean up and learned about organic, inorganic, and B3 waste through easy-to-understand materials such as pamphlets and posters. The posters explained how to sort trash in a simple way that people could follow. The community was very active and happy to take part. The results were a cleaner environment and more people knowing how to sort their trash properly. This event also brought the students and local residents closer together. The hope is that this activity will help the community keep their area clean and take care of the environment on their own for the future.